2004
DOI: 10.1088/0305-4470/37/37/003
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic corrections in the two-dimensional Ising model in a random surface field

Abstract: In the two-dimensional Ising model weak random surface field is predicted to be a marginally irrelevant perturbation at the critical point. We study this question by extensive Monte Carlo simulations for various strength of disorder. The calculated effective (temperature or size dependent) critical exponents fit with the field-theoretical results and can be interpreted in terms of the predicted logarithmic corrections to the pure system's critical behaviour.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…Then one calculates β 1 = 0.499 (2). It is in good agreement with the surface exponent β s = 1/2 for the free surface [56]. Now, the exponent β 0 /ν is estimated to be 0.374.…”
Section: A Magnetizationsupporting
confidence: 67%
See 1 more Smart Citation
“…Then one calculates β 1 = 0.499 (2). It is in good agreement with the surface exponent β s = 1/2 for the free surface [56]. Now, the exponent β 0 /ν is estimated to be 0.374.…”
Section: A Magnetizationsupporting
confidence: 67%
“…For a large s, careful analysis shows that the power-law behavior is not perfect [55]. In the equilibrium state, one may show that the surface exponent β s of the disordered surface remains 1/2, but with a logarithmic correction to scaling [56]. Therefore, we fit the timedependent magnetization at x = 0.5 with a logarithmic correction to scaling, i.e., M(t) = c 1 t −α 1 /(1 + c 2 ln(t)) 1/2 , and derive α 1 = 0.231, consistent with β 1 /νz = 0.231(1) for the free surface.…”
Section: A Magnetizationmentioning
confidence: 99%
“…In the two-dimensional semi-infinite Ising model the perturbation caused by the random surface field is marginal so that the criterion does not yield a definite answer. This case was studied subsequently in [242,243,244,245] where it was shown that the surface critical behaviour of the 2d Ising model is described by Ising critical exponents with logarithmic corrections to scaling. For the special transition point, the Harris like criterion of [227] indicates that random surface fields are relevant in dimensions d ≤ 4.…”
Section: Semi-infinite Systems With Surface Imperfectionsmentioning
confidence: 99%
“…This type of star-like geometry has already been investigated for different type of problems: for the classical and quantum Ising models [26][27][28][29][30][31][32], wetting [33], self-avoiding random walks, percolation [32] etc. For the Ising model, the limit M → 0 corresponds to the problem of random boundary field [26,27,34]. The multiple junction could be a simplified model for describing the behavior of the contact process on complex networks composed of long, one-dimensional segments and rarely located junction points, in the vicinity of junctions.…”
Section: Introductionmentioning
confidence: 99%